Віртуальні активи: державне регулювання, оцінка, оподаткування - Косторной, Сергій Володимирович; Kostornoi, Serhii (Запоріжжя : 2023, 2023)
UA: Обіг віртуальних активів, зокрема криптовалют, набуває все більшого поширення в світі. Але в Україні відсутнє повноцінне законодавче забезпечення цього процесу, недостатньо врегульовані питання оцінки віртуальних активів та оподаткування доходів від операцій з ними. В статті розглянута класифікація віртуальних активів та зміни до неї з врахування європейських вимог та стандартів. Проаналізовані законопроекти щодо оподаткування операцій з віртуальними активами, основні підходи до оцінки та оподаткування віртуальних активів. EN: The circulation of virtual assets, in particular, cryptocurrencies, is becoming more and more widespread in the world. But in Ukraine, there is no full-fledged legislative support for this process, the issues of valuation of virtual assets and taxation of income from transactions with them are not sufficiently regulated. The article considers the classification of virtual assets approved in Ukraine, which provides for their division into unsecured and secured virtual assets. Proposed changes to it taking into account European requirements and standards (MiCA), namely: - electronic money tokens. - tokens linked to assets; - virtual assets that are defined by individual characteristics (NFT); - virtual assets that are not asset-linked tokens and electronic money tokens. Analyzed draft laws on taxation of operations with virtual assets, main approaches to valuation and taxation of virtual assets. An important issue is the correct assessment and declaration of virtual assets, in particular, cryptocurrencies. The main aspects that need to be paid attention to are the following: - identification and designation of the type and name of the virtual asset (cryptocurrency); - determination of the number of tokens or coins as of the last day of the reporting period; - determining the date of acquisition of cryptocurrency; - determination of the cost (based on the actual costs incurred by transferring funds from a bank account in exchange for the purchased cryptocurrency, and if this method cannot be used - on the basis of statistical data collected by specialized services). The following proposals have been formulated regarding the system of taxation of operations with virtual assets: - taxation at the stage of selling a virtual asset (exchange for money); - a tax agent is an organization that provides services related to transactions with virtual assets; - not to apply taxation regarding the creation, mining, ownership of virtual assets, as well as the exchange of one virtual asset for another; - minimum tax rates; - simple accounting and reporting procedure; - grace period – 5 years, during which zero rates of personal income tax and corporate income tax are applied.
Virtual assets: government regulation, assessment, taxation
Keywords: віртуальні активи; криптовалюти; токени; оцінка; оподаткування; MiCA; virtual assets; cryptocurrencies; tokens; valuation; taxation